Health + the Arts : Visual Identity System : Foster Gallery Exhibition - Roth, Richard; Cranston, Roy; Bulger, Amanda; Kantor, Mel L.; Kim, Hyunjoo (My University, 2019)
The goal of this project was to develop a visual identity system and promotional design materials for the latest Foster Gallery exhibit, "Health + the Arts" on UW-Eau Claire’s campus. This exhibition explored the intersection of health and the arts from different perspectives: health and healing as represented in art, and art as a form of healing. Our approach was to display the fundamental theme of the exhibit and be able to promote it in a visual solution that made sense to the public. The design solution took the form of the two entities - health and the arts - visually colliding and intersecting in space, describing the theme and spectacle of the exhibit. This process and method manifested itself into a logo, promotional posters, information designs, advertisements, digital pieces and signage designs for the exhibit. This research project provided an authentic scholarly and field experience for us by exposing to and solving the complex, multidisciplinary and pragmatic problems.
Color poster with text and images.
Keywords: Visual identity system; Promotional design; Art exhibitions; Posters